First report of oospore formation in Plasmopara viticola, the causal agent of grapevine downy mildew, in highland regions of southern Brazil - Bitencourt C. (2021)
© 2021 British Society for Plant PathologyThis work evaluates the formation of oospores of Plasmopara viticola, the causal agent of grape downy mildew (DM), in highland regions in southern Brazil. Leaves of susceptible and resistant grape genotypes naturally infected with the pathogen were collected in the autumn of 2017, 2018, and 2019 from vineyards located in the highlands of Santa Catarina state. Leaf tissues were evaluated by light microscopy and scanning electron microscopy. Oospores of P. viticola were identified in both susceptible and resistant host genotypes. They were concentrated in the central regions of the DM lesions, close to the leaf veins, and exhibited a rounded shape, yellowish colour, thick wall, and a diameter ranging from 16.28 to 49.15 µm. The formation of oospores is strong evidence that sexual reproduction is occurring in P. viticola in the climatic conditions of the highlands of southern Brazil. Sexual reproduction contributes to the maximization of genetic diversity via meiosis. Populations with high genetic variability are more likely to break resistance mechanisms conferred by resistance genes and to develop resistance to fungicides applied for disease control. To our knowledge, this is the first scientific study to prove the formation of P. viticola oospores in Brazil. The results presented provide a solid basis for further studies on sexual recombination in P. viticola. Genetic improvement programmes for grapevines, disease management methods, and disease prediction models need to consider the sexual reproduction of this pathogen, otherwise their effectiveness may be compromised.